2019
DOI: 10.18009/jcer.639384
|View full text |Cite
|
Sign up to set email alerts
|

Matematik Öğretmenlerinin ve Öğretmen Adaylarının Kavram Yanılgılarına Yönelik Öğretimsel Açıklamaları: Olasılık Konusu

Abstract: The aim of this study is to examine the awareness of mathematics teachers and preservice teachers on misconceptions related to the subject of probability and their instructional explanations about which methods should be used to correct these misconceptions. The study was carried out with six mathematics teachers and three preservice teachers studying in the 4th grade of a state university's secondary school mathematics teaching program. The case study method was used in the study. The interview form consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Our findings also confirm Díaz and Fuente's (2007) findings that the different biases in conditional probability reasoning tend to appear unrelated to one another, and sometimes appear opposed or related to some other components of understanding conditional probability problems. Furthermore, our findings are in accordance with Bursali and Ozdemir's (2019) findings. Their research suggested that teachers and pre-service teachers generally successfully identify some types of probabilistic misconceptions, at the same time not noticing other types.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings also confirm Díaz and Fuente's (2007) findings that the different biases in conditional probability reasoning tend to appear unrelated to one another, and sometimes appear opposed or related to some other components of understanding conditional probability problems. Furthermore, our findings are in accordance with Bursali and Ozdemir's (2019) findings. Their research suggested that teachers and pre-service teachers generally successfully identify some types of probabilistic misconceptions, at the same time not noticing other types.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our study contributes to studies on misconceptions, fallacies and biases present in conditional probability reasoning, and the influence of context (Carles & Huerta, 2007;Olgun & Isiksal-Bostan, 2019), as well as to studies on intuitions (Fischbein & Schnarch, 1997). Furthermore, it also relates to existing studies on pre-service mathematics teachers' understanding of probability (Batanero et al, 2015;Bursali & Ozdemir, 2019;Estrada & Batanero, 2006;Goméz-Torres et al, 2016;Hokor, 2020;Ozen, 2013) and to studies on using media in teaching probability and statistics (Kus & Cakiroglu, 2020;Ozen, 2013;Watson, 1997). We also aim to obtain some new ideas for development of the future teaching of conditional probability, since "If one investigates the student's difficulties and misconceptions, one does not identify only logical deficiencies.…”
Section: Research Articlementioning
confidence: 58%
See 1 more Smart Citation
“…When we examine the answers given by the participants to the questions examining the probability bias (11), equiprobability bias (8), and the outcome approach (12), which are the probability misconceptions that teachers or preservice teachers have the most problems with, we observe that the questions with the lowest points are the questions. We can claim that the results coincide with previous literature (Bursalı & Gökkurt-Özdemir, 2019;Hourigan & Leavy, 2019;Stohl, 2005). We can also conclude that the participants' ACK and SCK about these concepts are quite insufficient.…”
Section: Classicalsupporting
confidence: 93%
“…Danişman & Tanışlı, 2017), in concepts of probability (ex. dependent probability, chance, sample space), which examine misconceptions and beliefs about probability (for example, Bursalı, & Gökkurt-Özdemir, 2019;Stohl, 2005), and which examines conceptual and procedural levels of knowledge about probability (e.g., Ata, 2014;Karaaslan & Ay, 2017;Kurt-Birel, 2017). A study to develop a test to measure teacher candidates' understanding of statistics and probability at a cognitive level is also a study that measures teacher candidates' statistical reasoning skills (Arican & Kuzu, 2020).…”
Section: Introductionmentioning
confidence: 99%